Progressive Corrosion Study of Metals like Mild Steel, Zinc and Aluminium in an Urban Atmosphere - H. K. Kadiya; R. T. Vashi (E-Journal of Chemistry)
Corrosion rate (Progressive) of mild steel (MS), zinc and aluminum have been determined under outdoor conditions of exposure at Valsad (South Gujarat) representing an urban atmosphere. Mild steel (MS), zinc and aluminium plates exposed during November 2005 indicates corrosion rate of 88, 33 and 1.4 mg/sq.dm for one month exposure period and 3668, 968 and 26.1 mg/sq.dm for mild steel, zinc and aluminium respectively for twelve months exposure period. Mild steel panels exposed vertically suffer less corrosion than those exposed at an angle of 45°. The resistivity towards the atmosphere was in the increasing order: mild steel < zinc < aluminium. Corrosion rate of these three metals found more in rainy seasons than the rate of winter and summer season